2015
DOI: 10.5194/acp-15-10471-2015
|View full text |Cite
|
Sign up to set email alerts
|

Global OZone Chemistry And Related trace gas Data records for the Stratosphere (GOZCARDS): methodology and sample results with a focus on HCl, H<sub>2</sub>O, and O<sub>3</sub>

Abstract: Abstract. We describe the publicly available data from the Global OZone Chemistry And Related trace gas Data records for the Stratosphere (GOZCARDS) project and provide some results, with a focus on hydrogen chloride (HCl), water vapor (H2O), and ozone (O3). This data set is a global long-term stratospheric Earth system data record, consisting of monthly zonal mean time series starting as early as 1979. The data records are based on high-quality measurements from several NASA satellite instruments and the Atmo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
131
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(136 citation statements)
references
References 96 publications
5
131
0
Order By: Relevance
“…The HF data record was not ready in time to be included in the original dataset provided for public usage (temperature, O 3 , H 2 O, HCl, N 2 O, and HNO 3 ); we are presenting the HF data for the first time here. Froidevaux et al (2015) have described the GOZCARDS data creation methodology and some stratospheric characteristics concerning the latter five species. The constituent datasets are time series of monthly zonal means vs. latitude (in 10 • latitude bins) taken from existing satellite datasets.…”
Section: Gozcardsmentioning
confidence: 99%
“…The HF data record was not ready in time to be included in the original dataset provided for public usage (temperature, O 3 , H 2 O, HCl, N 2 O, and HNO 3 ); we are presenting the HF data for the first time here. Froidevaux et al (2015) have described the GOZCARDS data creation methodology and some stratospheric characteristics concerning the latter five species. The constituent datasets are time series of monthly zonal means vs. latitude (in 10 • latitude bins) taken from existing satellite datasets.…”
Section: Gozcardsmentioning
confidence: 99%
“…[a] in situ data we also use AoA calculated from the satellitebased GOZCARDS (Global OZone Chemistry And Related trace gas Data records for the Stratosphere, Froidevaux et al, 2015) N 2 O data, using the empirical relationship of N 2 O with AoA (see Andrews et al, 2001;Linz et al, 2017) (2001) were not reported with uncertainties. Moreover, AoA determined from GOZCARDS N 2 O data is used (gray circles) (Andrews et al, 2001;Linz et al, 2017).…”
Section: Tropical Upwellingmentioning
confidence: 99%
“…We used a 10 • × 20 • grid to construct monthly mean data. We followed the method of Froidevaux et al (2015) for merging the satellite data in the present work. Merging is done by computing average relative biases between the source data sets during the overlapping periods and then applying additive offsets to each source of data to adjust them to a common reference to remove relative biases.…”
Section: Merging Of Satellite Datamentioning
confidence: 99%